The Development of a Semantic-based Image Retrieval Model by Pre-training Neural Network - Santirattanaphakdi, Chakkarin; Niwattanakul, Suphakit (Journal of Science Ladkrabang, 2023)
This research aims to develop a semantic-based image retrieval model applying the Contrastive Language-Image Pre-training (CLIP) model. Evaluation of image retrieval performance with precision, recall and f-measure, it was found that image search results with the query by global labels condition and the query by high level concepts of the images condition had a very good level of precision, the model can efficiently retrieve images from the content. However, image retrieval results with the query by qualitative semantic concepts of the image condition, despite having a good level of precision. But the results are far from the user's expectations because the semantic of image is interpreted by experience on human perception principles. In addition, also, the semantic of image is difficult to evaluate whether they are correct or not. The output from this research can resolve the semantic gap problem and support users by query within a natural language that attaches to the semantic of the image rather than the grammar of the language. This impact of results in a guideline for semantic information retrieval in the future.